Assessment of Quadratic Nonlinear Cardiorespiratory Couplings During Tilt Table Test by Means of Real Wavelet Biphase - Kontaxis, Spyridon; Lázaro, Jesús; Gil, Eduardo; Laguna, Pablo; Bailón, Raquel (Jornada de Jóvenes Investigadores del I3A, 2017)
In this paper a method for the assessment of Quadratic Phase Coupling (QPC) between respiration and Heart Rate Variability is presented and applied to study cardiorespiratory couplings during a tilt table test. Strong QPC related to the dominant respiratory frequency is present and remains unchanged during Autonomic Nervous System changes.